Impact of Quercetin on Oxidative Stress and Sperm Function in Leukocytospermic Subfertile Men - Qurat-ul-ain Fatima; Sadia Rehman; Faizania Shabbir; Nargia Haider; Hina Moazzam; Aliya Ishaque (Pakistan Journal of Medicine and Dentistry)
Background: Leukocytospermia, which is defined as the substinence of a raised amount of white blood cells in seminal fluid, is generally correlated with male subfertility. It causes oxidative stress, influencing the motility and morphology of sperm and its DNA integrity. The objective of the study is to investigate the association between leukocytospermia (as a marker of oxidative stress) and impaired seminal constraints in subfertile men, and to evaluate the role of quercetin—a natural antioxidant—in taming sperm quality, motility, and overall outcomes of fertility.